PRELIMINARY STUDY ON THE DEVELOPMENT OF A GROUND MOTION PREDICTION EQUATION (GMPE) FOR BALI ISLAND - Mursyida, Qisthi; Rudyanto, Ariska; Suardi, Iman; Ridwan, Egidio (Prodi Fisika FST UNJA, 2026)
Bali Island is a region with high tectonic activity due to the interaction between the Indo-Australian and Eurasian Plate, as well as the presence of active faults in the surrounding area. Consequently, the region is highly susceptible to earthquakes, while GMPE models that specifically represent the local seismotectonic characteristics of Bali remain limited. This study aims to classify earthquake sources around Bali into shallow crustal, interface, and intraslab earthquakes, develop GMPE models for each source type, and evaluate the resulting ground motion attenuation characteristics. The study utilized earthquake records from 151 BMKG FBA and MEMS stations collected between 2017 and 2024, covering a moment magnitude range of 2.0-6.9. Earthquake source classification was conducted based on depth and magnitude criteria and subsequently validated using cross-section analysis of the USGS slab model. The classification identified 800 earthquake events, consisting of 491 interface earthquakes, 157 intraslab earthquakes, and 152 shallow earthquakes. The GMPE models were developed by recalibrating the coefficients of an existing GMPE models using moment magnitude, source to site distance, hypocentral depth, and local site effect as predictor variables. Model performance was evaluated using the Log-Likelihood (LLH) and Euclidean Distance-Based Ranking (EDR) methods. The evaluation results indicate that the modified GMPE consistently outperformed the original model for all earthquake source types. Furthermore, the modified model produced attenuation patterns that were more consistent with the observed ground motion data, particularly at larger source to site distances.